Tourism, gender and development. An ethnic case in Morocco - BERLANGA ADELL, María Jesús (Revista Iberoamericana de Estudios de Desarrollo)
This article is based on the author’s Ph.D. research on the relationship between tourism and the development it generates in the Berber ethnic group in Aït Haddidou (living in High Atlas mountains of Morocco). This patriarchal and cattle-raising society went through a wide process of transformation in the 1980s, evolving from a subsistence economy to a precarious market economy. The development model the community is following is generating an increase in inequality between men and women, with the women’s loss of power as a consequence. In this context, tourism has become one of the main economic resources.However, it just reinforces this tendency towards the increase in gender inequality, progressively giving more political and economic power to the male community to the detriment of women.